Here/There and Somewhere Else: The Artistic Connections of Jiří Valoch with Former Yugoslav Territory during the 1960s and 70s - Ivana Janković (Miejsce)
This case study aims to examine the artistic connections and exchanges of ideas that Jiří Valoch made within the territory of then-Yugoslavia during the 1960s and 70s. The study is based on works and the rich correspondence from the Zagreb-based Marinko Sudac Collection, the Zagreb Museum of Contemporary Art’s Archive and Collection, and the Croatian Academy of Sciences and Arts’ Fine Arts Archives in Zagreb.